“The Nuruls”: A Sociolinguistic Study of Name Enregisterment in Indonesian Online Discourse - Fakhira, Rifda; Amaly, Najla (UIN Antasari Banjarmasin, 2024)
The emerging trend of using first name as a register to address a specific kind of social and linguistic behaviour has been getting more common. This phenomenon is related to a linguistics process that is known as enregisterment (Agha, 2003). The current study examines the enregisterment process of the name